Immunomodulatory Effects of RAAS Inhibitors: Beyond Hypertension and Heart Failure - Raluca Ecaterina Haliga; Elena Cojocaru; Oana Sîrbu; Ilinca Hrițcu; Raluca Elena Alexa; Ioana Bianca Haliga; Victorița Șorodoc; Adorata Elena Coman (Biomedicines)
The renin–angiotensin–aldosterone system (RAAS) plays a central role in cardiovascular and renal homeostasis and is increasingly recognized for its broad immunomodulatory effects. Pharmacological RAAS inhibition, primarily via angiotensin-converting enzyme inhibitors (ACEIs) and angiotensin receptor blockers (ARBs), has demonstrated therapeutic value beyond its use in hypertension and heart failure, extending to autoimmune, infectious, oncologic, and neurodegenerative conditions. ACEIs and ARBs modulate both innate and adaptive immune responses through Ang II-dependent and -independent mechanisms, influencing macrophage polarization, T-cell differentiation, cytokine expression, and antigen presentation. Notably, ACEIs exhibit Ang II-independent effects by enhancing antigen processing and regulating amyloid-β metabolism, offering potential neuroprotective benefits in Alzheimer’s disease. ARBs, particularly telmisartan and candesartan, provide additional anti-inflammatory effects via PPARγ activation. In cancer, RAAS inhibition affects tumor growth, angiogenesis, and immune surveillance, with ACEIs and ARBs showing distinct yet complementary impacts on tumor microenvironment modulation and chemotherapy cardioprotection. Moreover, ACEIs have shown promise in autoimmune myocarditis, colitis, and diabetic nephropathy by attenuating inflammatory cytokines. While clinical evidence supports the use of centrally acting ACEIs to treat early cognitive decline, further investigation is warranted to determine the long-term outcomes across disease contexts. These findings highlight the evolving role of RAAS inhibitors as immunomodulatory agents with promising implications across multiple systemic pathologies.